2011
DOI: 10.2168/lmcs-7(2:8)2011
|View full text |Cite
|
Sign up to set email alerts
|

On the Correspondence between Display Postulates and Deep Inference in Nested Sequent Calculi for Tense Logics

Abstract: Abstract. We consider two styles of proof calculi for a family of tense logics, presented in a formalism based on nested sequents. A nested sequent can be seen as a tree of traditional single-sided sequents. Our first style of calculi is what we call "shallow calculi", where inference rules are only applied at the root node in a nested sequent. Our shallow calculi are extensions of Kashima's calculus for tense logic and share an essential characteristic with display calculi, namely, the presence of structural … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
101
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(103 citation statements)
references
References 17 publications
2
101
0
Order By: Relevance
“…[5,6,16,14,15,11] introduce methods to extract rules out of suitable Hilbert axioms. More precisely [5,6] generate sequent and hypersequent rules, [11] nested sequent rules, [15] sequent rules for certain modal axioms, and [16] labelled rules; finally [14] transforms suitable modal and tense axioms (called primitive tense axioms) into structural rules for the display calculus. [14] also provides a characterisation as it is shown that each such rule added to the base system is equivalent to the extension of the logic by primitive tense axioms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5,6,16,14,15,11] introduce methods to extract rules out of suitable Hilbert axioms. More precisely [5,6] generate sequent and hypersequent rules, [11] nested sequent rules, [15] sequent rules for certain modal axioms, and [16] labelled rules; finally [14] transforms suitable modal and tense axioms (called primitive tense axioms) into structural rules for the display calculus. [14] also provides a characterisation as it is shown that each such rule added to the base system is equivalent to the extension of the logic by primitive tense axioms.…”
Section: Introductionmentioning
confidence: 99%
“…All the above results start with a specific logic and introduce calculi for (some of) its axiomatic extensions, e.g., Full Lambek calculus with exchange FLe for [5,6], or the tense logic Kt for [14,11]. This paper proposes instead a recipe that utilises the more common Hilbert axioms to construct analytic calculi 1 .…”
Section: Introductionmentioning
confidence: 99%
“…right-sided) if in its positive (resp. negative) signed generation tree, 32 every positive node is labelled with a structural connective which is associated with a logical connective when occurring in antecedent position, and every negative node is labelled with a structural connective which is associated with a logical connective when occurring in succedent position.…”
Section: Soundness Completeness Conservativitymentioning
confidence: 99%
“…In recent years, these questions have been intensely investigated in the context of various proof-theoretic formalisms (cf. [39,6,10,32,7,36,34,38,35]). Perhaps the first paper in this line of research is [33], which addresses these questions in the setting of display calculi for basic normal modal and tense logic.…”
mentioning
confidence: 99%
“…calculus [14,2] is a popular proof formalism that has been used to present intuitionistic logic [7], conditional logics [18], logics in the classical and intuitionistic modal cube [14,22,15] and path axiom extensions of classical modal logic [12]. The idea is to use a tree of traditional sequents as the basic building block rather than just a single traditional sequent.…”
Section: Introductionmentioning
confidence: 99%